Analisis Potensi Komoditas Kopi Kabupaten/Kota di Indonesia Tahun 2015: Metode Fuzzy C-Medoid Clustering - Zikra, Adilla; Dhardiri, Hudan; Yulianti, Susi (University of Islam Malang, 2022)
Indonesia is one of the largest producing and exporting countries of coffee in the world. 90% of coffee plantations in Indonesia are empowered by small farmers. By that, the development of coffee production in Indonesia has a great influence to the improvement of the welfare of people with middle to lower economic capacity and is able to encourage inclusive economic growth. However, until now Indonesia's coffee production still has a weak competitiveness compared to the other three exporting countries. The quality of Indonesian Arabica and Robusta coffee beans as export varieties is relatively low, causing the Indonesian coffee market share to be threatened. This reflects that the government's efforts to improve the quality and production of coffee are not optimal and not well targeted. Those efforts will run more effectively and efficiently when it’s applied to areas with high coffee production potential. Therefore, this study aimed to analyze which regions in Indonesia that have potential for coffee production and group them into clusters according to the characteristics of each region they have. The data in this study were sourced from the Indonesian Coffee Statistics Publication of the Directorate General of Plantations, Ministry of Agriculture in 2015 and the analytical method used is a descriptive method with graphs and Fuzzy C Medoid Clustering. The results of the robusta coffee clustering show that there are 28 districts/cities classified as high potential to develop this type of coffee with the characteristics of coffee plantation area, percentage of undamaged coffee plantation land, coffee productivity, and a high number of coffee farmers. Meanwhile, for Arabica coffee, there are 32 regions/cities classified as high potential with the characteristics of coffee plantation area and large number of coffee farmers. These results can be utilized by the local government as well as the central government to focus on the development of coffee production in these districts/cities.